A Forward Look At Noninvasive Prenatal Testing. Issue 11 (November 2016) - Liu, Li; Li, Kang; Fu, Xin; Chung, Christopher; Zhang, Kang
Abstract : Genomic abnormalities are a leading cause of birth defects and pregnancy complications, including in utero growth retardation and risk of miscarriage. Traditional invasive methods detecting such genomic abnormalities pose a relative risk to mother and unborn fetus. Non-invasive prenatal testing (NIPT) is a method that determines the genomic status of a fetus in utero by analyzing circulating fetal DNA in maternal plasma or serum. This review comes at a time when more and more physicians and hospitals might be using NIPT; there is great potential in extending this technology to other diagnostic applications. We discuss here the most current advances in diagnostic NIPT, its applications and limitations, as well as the development of future technology and possible clinical applications. Trends: Whole-genome chromosomal aneuploidy can be accurately diagnosed with high sensitivity and specificity using NIPT based on massively parallel sequencing techniques. Subchromosomal abnormalities can also be detected via sequencing and are useful in the detection of large insertion/deletion mutations. Monogenic disease diagnosis is carried out using several strategies including a relative mutation or haplotype dose strategy, targeted single molecular amplification, and sequencing.